Geografia econômica do SUS brasileiro: avanços, crises e o papel do Estado - Heimann, Moacir Roberto (2024)
This thesis analyzes the relationship between State policies, the economy, and advances and crises in the Unified Health System between the years 2000 and 2024. The role of the State in creating conditions conducive to the industrial productive organization and in the creation of public health systems health is central to the analysis. The central hypothesis is that the State, by organizing the conjunction of factors such as techno-scientific discoveries in chemical industrial production such as the production of medicines and health equipment, together with the creation of health systems to implement disease control policies, was and is mainly responsible for the development of the health industry sector. The thesis, based on extensive bibliography and use of health data, was able to demonstrate that the Unified Health System (UHS) is responsible for a set of social improvements that can be measured with different variables; 1- reduction of diseases; increase in life expectancy; reduction in the infant mortality rate; disease reduction; sanitary control; 2- expansion of physical health infrastructure, including Basic Health Units, Health Posts, Hospitals, and beds: expansion of the UHS across the territory and coverage of basic, medium, and high-complexity care; 3- in education and health: increase and health care coverage; of health professionals, doctors, nurses, dentists, pharmacists, and nursing technicians that allows the creation of new Family Health Teams (FHTs); 4- in industrial policies of the Health Industrial Economic Complex (HIEC); expand national production of priority items for the UHS reducing dependence on foreign inputs, medicines, vaccines, and other health products; in the economy: generating jobs and increasing national production. We also reflect on the effects of the political-economic crisis that began in 2014, affecting investments in health, showing that between 2015 and 2022, a period in which governments adopted austerity policies with a reduction in public spending per capita, it decreased, affecting the capacity of UHS to serve the population, increasing disparities in access to health services, deepened with the approval of the Spending Ceiling. Between 2016 and 2022, investments in public health fell 64%, from R$16.8 billion to R$6.4 billion. COVID 19 pandemic: shortages ranging from basic to more complex items to combat the pandemic. During the pandemic, measures were taken, and there was a temporary increase in resources allocated to health, however, these resources, the result of extraordinary measures, lost their effect as soon as the end of the pandemic emergency was declared. These factors combined show how the political and economic crisis negatively affected investments in health in Brazil, resulting in significant challenges for the public health system. With the political change that occurred in 2022/23, a new State project was inaugurated, aimed at resuming and creating new health projects; The New PAC and the National Strategy for the Development of the Health Economic-Industrial Complex, which aim for investments of R$42 billion by 2026 in the health area.